Numerical Investigation on MHD Marangoni Convective Flow of Nanofluid through a Porous Medium with Heat and Mass Transfer Characteristics - Venkateswara Raju, K.; Durga Prasad, P.; C. Raju`, M.; Sivaraj, R. (International Journal of Engineering and Technology, 2018)
The present study investigates on a steady two-dimensional Marangoni convective flow of nanofluid through a porous medium with heat and mass transfer characteristics. The proposed mathematical model has a tendency to characterize the radiation and chemical reaction effects. The governing equations in the form of partial differential equations have been converted into ordinary differential equations through similarity transformations, which have been solved by using Runge-Kutta method via shooting technique. The characteristics of velocity, temperature and concentration boundary layers are studied for different physical parameters. The local Nusselt and Sherwood numbers are estimated and discussed for aforesaid physical parameters. It is to be noted that the Marangoni ratio parameter is improves the rate of heat transfer and decreases the mass transfer rate.Â Â Â